Effects of FACTS devices on power system performance in view of small-signal or great disturbances - Colvara, Laurence Duarte; Festraits, Ednilton Bresson; Araujo, Silvio Cesar Braz (Institute of Electrical and Electronics Engineers (IEEE), 2003)
The problem of power system stability including the effects of Flexible Alternating Current Transmission System (FACTS) is approached. The Controlled Series Compensator and the Static Var Compensator (SVC) are considered, and their effects upon synchronizing and damping torque are analyzed by means of the properties of the potential part of the transient energy as well as the ones of the Lyapunov Function time derivative. © 2003 IEEE.
Keywords: Direct methods; Energy function; FACTS; Power system stability; SVC; TCSC